Factors Determining the Metal Ion Binding Ability and Selectivity of Hydroxamate-Based Compounds - Bíró, Linda; Buglyó, Péter; Farkas, Etelka (Current Medicinal Chemistry, 2021)
There has been a long tradition for a broad spectrum of applications of both natural and synthetic hydroxamic acids and derivatives. Even nowadays, a huge number of newly designed representatives (from different monohydroxamate-based compounds to siderophore conjugates) are used to develop potential drug candidates with desired activities. Since these compounds are effective metal-chelating agents, their biological roles and actions as well as their various applications, e.g., in the medicinal practice, are all in direct correlation with their metal complexation. Consequently, the knowledge of the stoichiometry and binding modes of metal complexes with hydroxamic acid-based ligands, their thermodynamic parameters, and speciation profiles in solution are crucial for scientists working in any of the above-mentioned fields. This review, in addition to presenting a few factors, which might affect the metal-binding capabilities of these organic ligands, displays and summarizes the different parameters typically used to give the stoichiometry, composition, and stability of the species formed in a solution equilibrium system in measurable concentration. Discussion of the possibilities for quantitative comparison of metal-binding effectivity and selectivity of various hydroxamic acids with each other by using solution equilibrium data is also the focus of this publication.
Keywords: metal-binding effectivity